KLASIFIKASI TINGKAT KEPARAHAN KEMISKINAN PROVINSI DI INDONESIA DENGAN ANALISIS DISKRIMINAN - Hendayanti, Ni Putu Nanik; Nurhidayati, Maulida (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Poverty is one of the main problems of the government that is prioritized in developing the development strategy of every country including Indonesia. The poverty rate in Indonesia is still relatively high, so the government focuses on decreasing the existing poverty level by improving the welfare of the population. Therefore, it is very important for the government to know the severity of poverty in Indonesia so that it can take a policy to reduce the existing poverty level. The purpose of the research was to group the severity of provincial poverty in Indonesia with a Discriminant Analysis. The stages of discriminant analysis include testing of normal multivariate distribution, testing of homogeneity of covariance variants, discriminant analysis by stepwise method, then continued calculation of classification accuracy value. The results of this research show that the large classification rate obtained is only 67.7% which means that not all provinces are able to be classified appropriately based on the variable open unemployment rate (TPT).